mGBP2 engages Galectin-9 for immunity against Toxoplasma gondii. - Elisabeth Kravets; Gereon Poschmann; Sebastian Hänsch; Veronica Raba; Stefanie Weidtkamp-Peters; Daniel Degrandi; Kai Stühler; Klaus Pfeffer (PLoS ONE)
Guanylate binding proteins (GBPs) are large interferon-inducible GTPases, executing essential host defense activities against Toxoplasma gondii, an invasive intracellular apicomplexan protozoan parasite of global importance. T. gondii establishes a parasitophorous vacuole (PV) which shields the parasite from the host's intracellular defense mechanisms. Murine GBPs (mGBPs) recognize T. gondii PVs and assemble into supramolecular mGBP homo- and heterocomplexes that are required for the disruption of the membrane of PVs eventually resulting in the cell-autonomous immune control of vacuole-resident pathogens. We have previously shown that mGBP2 plays an important role in T. gondii immune control. Here, to unravel mGBP2 functions, we report Galectin-9 (Gal9) as a critical mGBP2 interaction partner engaged for immunity to T. gondii. Interestingly, Gal9 also accumulates and colocalizes with mGBP2 at the T. gondii PV. Furthermore, we could prove the requirement of Gal9 for growth control of T. gondii by CRISPR/Cas9 mediated gene editing. These discoveries clearly indicate that Gal9 is a crucial factor for the mGBP2-coordinated cell-autonomous host defense mechanism against T. gondii.